2008
DOI: 10.1002/path.2357
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme 2 (ACE2) expression and activity in human carotid atherosclerotic lesions

Abstract: Angiotensin-converting enzyme (ACE)2 is a recently identified homologue of ACE. As ACE2 inactivates the pro-atherogenic angiotensin II, we hypothesize that ACE2 may play a protective role in atherogenesis. The spatiotemporal localization of ACE2 mRNA and protein in human vasculature and a possible association with atherogenesis were investigated using molecular histology (in situ hybridization, immunohistochemistry). Also, the ACE : ACE2 balance was investigated using enzymatic assays. ACE2 mRNA was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 20 publications
7
98
2
Order By: Relevance
“…Furthermore, they also found that ACE2 activity was lower in stable atherosclerotic plaque compared with vulnerable plaque, suggesting that ACE2 activity was regulated in atherosclerosis in different period and progression of atherosclerotic plaque. 23 Our study showed that AngII was involved in the down-regulation of expression/activation of ACE2 in the in vitro study. Other research has shown that hyperglycemia was positively correlated with ACE2 activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, they also found that ACE2 activity was lower in stable atherosclerotic plaque compared with vulnerable plaque, suggesting that ACE2 activity was regulated in atherosclerosis in different period and progression of atherosclerotic plaque. 23 Our study showed that AngII was involved in the down-regulation of expression/activation of ACE2 in the in vitro study. Other research has shown that hyperglycemia was positively correlated with ACE2 activity.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, our previous study and other study demonstrated that ACE2 protein was also expressed in endothelial cells, SMCs and macrophages in atherosclerotic plaque. 14, 23 Sluimer et al found that ACE2 protein was present in atherosclerotic carotid arteries and that ACE and ACE2 protein were expressed in total vessel wall during all stages of atherosclerosis. Furthermore, they also found that ACE2 activity was lower in stable atherosclerotic plaque compared with vulnerable plaque, suggesting that ACE2 activity was regulated in atherosclerosis in different period and progression of atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, overexpression of ACE2 in the heart has been reported to cause several disadvantages, 14 demonstrating the complexity of the renin-angiotensin system. ACE2 mRNA expression has been shown to localize in atherosclerotic lesions 15 as well as in endothelial cells in humans, 16 where most of the mechanical stresses are acting (one such stress is pressure, and thus pressure was used in this study). ACE2 mRNA expression has been reported to be decreased in most of the cardiovascular diseases, 17,18 and in an adult hypertensive model, 19 including human renal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…39,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Recently, CEUS imaging of the carotid artery provided a novel, non-invasive method for directly examining plaque vascularity; perhaps providing a ''window'' into plaque vulnerability. Historical consideration of the vasa vasorum.…”
Section: Identification Of Adventitial and Intraplaque Angiogenesis (mentioning
confidence: 99%
“…72 The presence of the immature microvessels (''leaky'' vessels) contribute inflammation materials by providing a source of noxious plasma components (hemoglobin, oxidized low-density lipoprotein cholesterol, lipoprotein[a], glucose, advanced glycation end products AGE) and inflammatory cells. 73,74 Ultimately, the atherosclerotic plaque, similar to the other abnormal tumor growths, requires nutrient blood flow supplied by arterial and venous vasa vasorum.…”
Section: Identification Of Adventitial and Intraplaque Angiogenesis (mentioning
confidence: 99%